Development of a Peltier-based chilled-mirror hygrometer, SKYDEW, for tropospheric and lower-stratospheric water vapor measurements - T. Sugidachi; M. Fujiwara; K. Shimizu; S.-Y. Ogino; J. Suzuki; R. J. Dirksen (Atmospheric Measurement Techniques)
We have developed a Peltier-based non-cryogenic chilled-mirror hygrometer named SKYDEW to measure water vapor from the surface to the stratosphere. Several chamber experiments were conducted to investigate the characteristics and performance of the instrument under various conditions. The stability of the feedback controller that maintains the condensate on the mirror depends on the controller setting, the condensate condition, and the frost point in ambient air. The results of condensate observation by a microscope and proportional-integral-derivative (PID) tuning in a chamber were used to determine the PID parameters of the controller such that slight oscillations of the scattered light signal from the mirror and mirror temperature are retained. This allows for the detection of steep gradients in the humidity profile, which are otherwise not detected because of the slower response. The oscillation of the raw mirror temperature is smoothed with a golden point method that selects the equilibrium point of the frost layer. We further describe the details of the data processing and the uncertainty estimation for SKYDEW measurements in terms of the Global Climate Observing System (GCOS) Reference Upper-Air Network (GRUAN) requirements. The calibration uncertainty of the mirror temperature measurement is < 0.1 K for the entire temperature range from −95 to 40 °C. The total measurement uncertainty of SKYDEW measurements can exceed 0.5 K in regions where large oscillations of the mirror temperature remain.